KEMANDIRIAN BELAJAR DITINJAU DARI KREATIVITAS BELAJAR DAN MOTIVASI BELAJAR MAHASISWA - Isnawati, Nina; Samian, Samian (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
The research aims are to know: 1) the influence of learning creativity towards studyindependence; 2) the influence of study motivation towards study independence, 3)the influence of learning creativity and study motivation towards studyindependence simultaneously. The research method used is descriptive quantitative.The population is all of students of UMS in 2010/11 period around 190, sample is123 by using simple random sampling technique. Data collecting used is questionnaire that wastested and fulfilled validity and reliability requirement. Analysis data used doubled linierregression Y = 10,163 + 0,452X1 + 0,349X2, based on analysis and discussion about students ofUMS in 2010 period can be concluded that: 1) learning creativity has positive influence towardsstudy independence, with significance value 0,000 0,05. (2) study motivation has positive influencetowards study independence, with significance value 0,000 0,05. (3) learning creativity and studymotivation towards study independence simultaneously have positive influence towards studyindependence, with significance value 0,000 0,05. (4) The contribution of R2 is 0.376, it means37,6% students study independence was influenced by learning creativity and study motivationvariables, the rest is 62,4% was influenced by other factors that did not follow in this research.